1974
DOI: 10.1021/ja00811a022
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of organic compounds with cerium(IV). XVIII. Oxidative decarboxylation of substituted phenylacetic acids

Abstract: Substituted phenylacetic acids are readily decarboxylated when treated with ceric ammonium nitrate in aqueous acetonitrile solutions containing nitric acid to give carbon dioxide and the corresponding benzyl alcohol, benzaldehyde, and benzyl nitrate. Oxygen-trapping experiments indicate that benzyl radicals are formed as intermediates. A Hammett plot of the relative rates of oxidation of meta-and para-substituted phenylacetic acids vs. + values gave a p of -2.91 ± 0.29. The oxidative decarboxylation is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 1 publication
6
35
0
1
Order By: Relevance
“…Based on the above results and previous reports,5c, 14–16, 19–23 we propose a plausible mechanism for Cu 0 ‐mediated deoxygenative trifluoromethylation of benzylic xanthates using Umemoto’s reagent 2 a (Scheme ). Reduction of 2 a by Cu 0 in situ provides CuCF 3 in addition to CuOTf 5c.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Based on the above results and previous reports,5c, 14–16, 19–23 we propose a plausible mechanism for Cu 0 ‐mediated deoxygenative trifluoromethylation of benzylic xanthates using Umemoto’s reagent 2 a (Scheme ). Reduction of 2 a by Cu 0 in situ provides CuCF 3 in addition to CuOTf 5c.…”
Section: Resultssupporting
confidence: 73%
“…This could be attributed to the weak Lewis acidic nature of CuOTf, which generates weak positive charge at benzylic position in the transition state 15a. b, 22 Alternatively, the small negative value for ρ + could be attributed to a pathway involving a benzylic radical cation intermediate 23. The reaction of 1 a with a pregenerated combination of CuCF 3 /CuOTf was inhibited in the presence of several radical scavengers, including 1,4‐dinitrobenzene, hydroquinone, and 2,2,6,6‐tetramethyl‐1‐piperidinyloxy [TEMPO, Eq.…”
Section: Resultsmentioning
confidence: 99%
“…2) range of 1.00-2.00 mol/dm3: at 25.0°C, k; = 18 dm3/mol s and k; = 37 mol/dm3 s. Moreover, if we consider the experimental condition at 2.00 mol/dm" sulfuric acid, we evaluate that k ; = 6.8 dm6/mo12 s, k i = 14 s-l, and k ; + ki/[H2S04]2 = 10.3 dm6/moI2 s. The latter value is in good agreement with that [see eq. (3)] obtained in H2S04-LiHS04 mixtures and gives a further support to the validity of the final rate equation (6) for the cerium(1V) oxidation of p-methoxymandelic acid.…”
Section: Resultssupporting
confidence: 70%
“…Anomalously high rates were also observed previously [6,7,15] in the oxidation of methoxy derivatives of several organic substrates containing a benzene ring and were generally ascribed to a change in the reaction mechanism. It was suggested that the methoxy group facilitates [IS] attack on the aromatic nucleus with the probable formation of an intermediate radical cation [6,7,15]. The same explanation can reasonably apply to the p-methoxy derivative of the present study.…”
Section: Resultssupporting
confidence: 69%
“…9. When WO 3 is illuminated, the photoelectrons would be excited from the valance band to conduction band and then transfer from the vertical-aligned WO 3 the organic enclosing the cobalt ion valency circle [29,30] and meantime the organic would be degraded. The CoOOH serving as hole trap could promote photogenerated carriers separation and improve photoelectrocatalytic degradation of MB over the WO 3 -CoOOH composite (Fig.…”
Section: The Photoelectrocatalytic Activity Of the Filmsmentioning
confidence: 99%